Excess and Partial Molar Volumes for [Difurylmethane+Acetonitrile] Binary Mixtures in the Temperature Range: 288.15— 323.15 K - A.A. DDAMBA, WILFRED (Asian Journal of Chemistry, 2010)
Densities of binary systems of difurylmethane in acetonitrile have been measured with an Anton Paar DMA 4500 vibrating-tube densimeter over the entire composition range at intervals of 5 K in the temperature range between 288.15 and 323.15 K and atmospheric pressure. Excess molar volumes (VmE) of mixtures, limiting ( ViE,∞) and excess partial ( ViE) molar volumes of components of the binary system have been examined to provide insight into the variation with temperature, of the intermolecular interactions and molecular packing efficiencies. The observed dependence of these functions on both composition and temperature has been discussed in terms of specific intermolecular interactions and structural effects.